Resiliensi Ekonomi Petani Cengkeh Menghadapi Masalah Gagal Panen (Studi di Desa Malewong Kecamatan Larompong Selatan) - Halimah, Andi Sitti (Universitas Galuh, 2025)
The decline in clove crop production due to crop failure in Malewong Village has required farmers to adapt to the situation. This ability is expected to restore the condition of their farms for sustainability. Their resilience actions in the form of social competence, problem solving skills, autonomy, sense of purpose and bright future are the focus of this study. This study aims to determine the economic resilience of clove farmers facing the problem of crop failure. In-depth interviews were conducted by random purposive sampling of clove farmers in the area. The results showed that clove farmers have an adaptive attitude driven by social support (I Have), self-strength (I Am), and ability (I Can) in their resilience to face the problem of crop failure. They use their social capital (social competence) to obtain loans as additional capital in crop maintenance efforts. Some farmers plant other crops such as patchouli, pepper, cacao and durian. There are also those who utilise their knowledge and skills to process unproductive clove tree trunks into profitable oil (problem solving skills). Other actions include intensive land clearing and fertilisation of clove plants (autonomy), and for the sustainability of their farms, farmers carry out plant rehabilitation by replacing old plants with seedlings of better varieties (sense of purpose and bright future) in the hope that production will increase.